The Influence Of The E-WOM, E-Trust, and E-Service on Purchase Decision: Study on TikTokShop Marketplace Users in West Jakarta - Sriyanto, Agus (Ridwan Institute, 2024)
The research aimed to investigate the influence of E-WOM, E-Trust, and E-Service on purchase decisions among active users of the TikTokShop marketplace in West Jakarta. These variables were chosen due to their critical roles in shaping consumer behavior and influencing purchasing decisions in online market contexts. E-WOM (Electronic Word of Mouth) reflects the power of recommendations and reviews from peers and online communities, which are crucial factors in modern consumer decision-making processes. E-Trust (Electronic Trust) is fundamental in establishing and maintaining relationships between consumers and online platforms, influencing user confidence in the platform's reliability, security, and credibility. E-Service (Electronic Service) directly impacts user experience and satisfaction within online marketplaces, as the quality of service provided significantly influences consumer perceptions and purchasing decisions. By examining the dynamics of E-WOM, E-Trust, and E-Service within the TikTokShop market context, the research aims to provide insights that can inform strategies to enhance user engagement, trust, and ultimately drive purchase decisions on the platform.